Changes in optical properties, structure and chemical composition of thin-film Ag-Pbl₂ systems at intercalation of ammonia - Mussil, V.V.; Lemeshevskaya, Ye.T.; Pilipenko, V.V.; Gurina, G.I. (Functional Materials, 2008)
The results of optical, electron microscopic and electron diffraction studies of film Pbl₂ and two-layer photosensitive Ag-Pbl₂ systems and changes thereof under ammonia intercalation are reported. The effect of intercalation on the photographic characteristics of the samples (photosensibility and contrast) has been established. The reversible changes in diffraction efficiency of photoinduced periodic structures have been revealed. The observed phenomena are discussed taking into account the concepts of the granular film optics and waveguide coatings, as well as of the chemical reaction kinetics.